2012
DOI: 10.1007/s10452-012-9415-y
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoecological evidence for changes over the past 200 years in chironomid communities of a shallow lake exposed to cyanobacterial toxins

Abstract: In spite of the existence of a number of papers applying the biomarker approach using pigments or akinetes to discuss the impact of cyanobacteria on the functioning of lakes in the palaeoenvironmental context, their sedimentary imprint in the form of microcystins (MCs) has never been taken into consideration. Our objective was to reconstruct 200 years of the development of chironomid assemblages in a shallow Polish lake with notoriously blooming toxic cyanobacteria. A 50-cm long sediment core sampled from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Microscopic algae, especially diatoms, are often rich in protein and essential fatty acids and may therefore be considered as high-quality food for growing larvae (Kajak and Warda 1968;Johannsson and Beaver 1983;Ahlgren et al 1997;Goedkoop et al 1997;Gullberg et al 1997;Dukowska et al 1999;Vos et al 2000). Cyanotoxins in turn can be accumulated in the tissues of chironomid larvae with no visible damage to the community, constituting an important vector of toxins to higher levels in aquatic food chains (Kaczorowska and Kornijów 2012;Toporowska et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic algae, especially diatoms, are often rich in protein and essential fatty acids and may therefore be considered as high-quality food for growing larvae (Kajak and Warda 1968;Johannsson and Beaver 1983;Ahlgren et al 1997;Goedkoop et al 1997;Gullberg et al 1997;Dukowska et al 1999;Vos et al 2000). Cyanotoxins in turn can be accumulated in the tissues of chironomid larvae with no visible damage to the community, constituting an important vector of toxins to higher levels in aquatic food chains (Kaczorowska and Kornijów 2012;Toporowska et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Palus et al (2007) reported a slight increase in DNA damage and frequency of micronuclei in human lymphocytes induced by selected cyanobacterial extracts (Microcystis aeruginosa, Aphanizomenon flos-aquae, Pseudoanabaena sp., and Anabaena sp.). In previous research on microalgae and micrograzer interaction (Berry et al, 2008;Kaczorowska and Kornijów, 2012;Toporowska et al, 2014), it was shown that the ingestion of different toxinproducing cyanobacteria can lead to the accumulation of toxins in Chironomus spp. larvae, as well as mortality and a decreased growth rate in Daphnia.…”
Section: Discussionmentioning
confidence: 99%
“…While records of historic MC production are slowly being produced and timelines are being extended, a comprehensive extraction technique and a detailed understanding of MC degradation and transformation post-deposition have yet to be established. As shown, the sedimentary MC content in the successive layers of sediment can demonstrate variability with no general trend of decrease [61,64]. This indicates that tracking their sedimentary content can be a reliable tool for following fluctuations in the development of MC-producers in the past.…”
Section: Microcystins (Mcs)mentioning
confidence: 99%